"Isotope effect" of hydrogen and deuterium interaction with vanadium alloys VCrTi. (2017) - Kenzhina, I.; Kulsartov, T.; Chikhray, Y.; Shestakov, V.; Tolebay, A.; Askerbekov, S.; Tazhibayeva, I.; Gordienko, Y.; Ponkratov, Y.; Zaurbekova, Zh.; Mukanova, A.
Abstract: V-Ti-Cr vanadium alloys have many perspective applications, particularly, they are considered as a main structural material of the first wall and blanket of fusion reactor with lithium coolant. Also, they are used as a high-temperature membrane for hydrogen isotopes separation and effective sorbents for hydrogen purification installations by PSA (Pressure Swing Adsorption) adsorption method (under the control of sorbent surface composition). The use of vanadium alloys can be extremely interesting because of the possibility of hydrogen isotopes separation in hydrogen systems. The fact is that vanadium has unique properties with respect to hydrogen: protium atoms typically occupy octahedral interstices in vanadium bcc lattice, while the deuterium atoms - mainly tetrahedral interstices. That all considerably affects diffusion and solubility of hydrogen isotopes in vanadium. This paper presents the results of experiments on sorption of hydrogen isotopes with V4Cr4Ti vanadium alloy from a mixture of hydrogen isotopes. According to the obtained time dependence of hydrogen isotopes partial pressure change in gas mixture the following parameters were determined: rate of dissolution and heat of dissolution of hydrogen and deuterium in vanadium alloys V4Cr4Ti, V10Cr5Ti. The conclusion about the prospects of using vanadium alloys in storage systems, separation and purification was made.